2021
DOI: 10.3390/brainsci11121644
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Causal Link between the Left Lateralization of Language and Other Brain Asymmetries? A Review of Data Gathered in Patients with Focal Brain Lesions

Abstract: This review evaluated if the hypothesis of a causal link between the left lateralization of language and other brain asymmetries could be supported by a careful review of data gathered in patients with unilateral brain lesions. In a short introduction a distinction was made between brain activities that could: (a) benefit from the shaping influences of language (such as the capacity to solve non-verbal cognitive tasks and the increased levels of consciousness and of intentionality); (b) be incompatible with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 173 publications
1
6
0
Order By: Relevance
“…On the other hand, the observation that the expansion of the cortical areas involved in voice processing selectively improved the results obtained for tasks of voice discrimination (and on the perceptual aspects of voice recognition) is consistent with the interpretations given by De Renzi [ 46 ] and Gazzaniga [ 47 ] about the greater role played by the right hemisphere in (visual, auditory, and somato-sensory) perception. These authors suggested that this asymmetry for perceptual functions could be interpreted in terms of neural plasticity (see Gainotti [ 48 ] for a recent review) assuming that the cortical areas involved in language processing in the left hemisphere have remained dedicated to perceptual functions in homologous areas of the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the observation that the expansion of the cortical areas involved in voice processing selectively improved the results obtained for tasks of voice discrimination (and on the perceptual aspects of voice recognition) is consistent with the interpretations given by De Renzi [ 46 ] and Gazzaniga [ 47 ] about the greater role played by the right hemisphere in (visual, auditory, and somato-sensory) perception. These authors suggested that this asymmetry for perceptual functions could be interpreted in terms of neural plasticity (see Gainotti [ 48 ] for a recent review) assuming that the cortical areas involved in language processing in the left hemisphere have remained dedicated to perceptual functions in homologous areas of the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations exploring the nonverbal cognitive abilities of aphasic patients (recently reviewed by Gainotti, 2021) have, indeed, confirmed Head's (1926) statement that these patients are not impaired on cognitive tasks that can be performed with simple perceptual activities, but are defective when intermediate (explicit or implicit) verbal formulations are required by the task. For instance, Baldo, Paulraj, Curran, and Dronkers (2015) showed a dissociation in performance of aphasic patients between two nonverbal tasks (picture completion vs. picture arrangement tasks of the Wechsler Adult Intelligence Scale) that require differing degrees of inner verbal reasoning.…”
Section: Emoji Use Validates the Potential For Meaning Standardizatio...mentioning
confidence: 84%
“…However, it is important to consider that only the total score was analyzed in this article, and individual protocol components were not considered. Future research may explore different language tasks and aspects of activity during lessons to determine whether a relationship exists between prosody [6,9], pragmatics [10], emotional [8] aspects of verbal communication, reading [11], and rightward functional hemispheric asymmetry. Also, sex differences may be considered in future research, as other studies have reported about the possible sex effect on lateralization [25].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the idea that right hemisphere activity is essential for certain aspects of language processing is emphasized in numerous studies. In a review [8], it was pointed out that the right hemisphere may encompass two primary brain systems to avoid interference with language tasks: the emotional system and the system responsible for orienting visual-spatial attention. Regions of the right hemisphere contribute to various crucial aspects of language processing, including prosody [6,9], pragmatic aspects of verbal communication in both native and foreign languages [10], and even reading [11].…”
Section: Introductionmentioning
confidence: 99%